Neoliberalism, Economic Radicalism, and the Normalization of Violence - Berdayes, Vicente; Murphy, John W.; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This compelling volume analyzes the wide-scale societal impact of neoliberal economic policy on contemporary life and behavior. Synthesizing perspectives from politics and economics with insights from psychology and linguistics, it argues that market-driven public institutions promote antisocial thinking, discourage critical reflection, and inure individuals to inequity and cruelty. Chapters cite the ubiquity of violence in modern society, from the marketing of the military to impersonal mass upheavals in the job market, as devaluing human worth and thus self-worth. But the editors also assert that these currents are not terminal, and the book concludes by identifying conditions potentially leading to a more civil and egalitarian future. Included in the coverage: The language of current economics: social theory, the market, and the disappearance of relationships. Neoliberalism and education: the disfiguration of students. Slicing up societies: commercial media and the destruction of social environments. Neoliberalism and the transformation of work. Economics, the network society, and the ontology of violence. A new economic order without violence. Given the centrality of economic events on the global stage, Neoliberalism, Economic Radicalism, and the Normalization of Violence stands out as both a springboard for discussion and a call to action, to be read by political and cultural economists, political scientists, and sociologists.
Keywords: International Economics; Economic policy; Sociology, general